Evaluasi Penyediaan Fasilitas Pengelolaan Sampah (Insinerator) Di Desa Kranggan - alfi andri; Evita Herawati Legowo; Kholis Abdurrahman Audah (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
Road map the community service of Swiss German University activities in 2016 until 2020 about manage of non-organic wasted. In addition, Keranggan village is used as the pilot project to implement the program of non-organic waste management which is located in district of Tangerang, Banten, Indonesia. Swiss German University provides non-organic waste tool to facilitate burn non-organic waste such as, banana peels and humid waste are name of few and its names as traditional incinerator. The objective to develop this tool is used the burn the waste and the waste may use for fertilizer and bricks manufacturer. At the same time, to educate the villagers to look after their environments and lead to life clean and healthy. The activity has been implemented in 2018 and therefore, monitoring and evaluating is implemented in 2019. The results shows that the incinerator was rarely used for burning waste and it impacts to the environment. It is an input for the SGU’s academic research center to find out another methods to improve the awareness of the villagers to utilize the incinerator tools that lead better environment